Perspectives on Dynamic Hardy–Littlewood Inequalities in Time Scale Analysis - Taher S. Hassan; Wafy M. Hasan; Ioan-Lucian Popa; Mouataz Billah Mesmouli; Akbar Ali; Haytham M. Rezk (Mathematics, 2025)
This study demonstrates several novel dynamic inequalities of the Hardy and Littlewood types on time scales. As special cases, our studies include Hardy’s integral inequalities and Hardy and Littlewood’s discrete inequalities. The research findings are demonstrated using algebraic inequalities, Hölder’s inequality, and the chain rule on time scales.